Investment efficiency of business in Ukraine: realities and assessment methodology - Sorokina, L.V.; Hoiko, A.F. (Ways to Improve Construction Efficiency, 2021)
The article systematized factors of investment attractiveness and investment climate in Ukraine. The expediency of supplementinganexistinglist of components of investment climate is substantiated by two additional factors. Themechanismo factionoftheproposedfactorsthatreflectthenegative effectin the developmen to freformsand innovations, aswellas the economic efficiency of construction projects on the financial result, expected from investigations, isrevealed. The trends in the developmen to finvestment activityinUkrainein 2015 - 2020, the existence of reserves for increasing the economic efficiency of investments and the need for their calculation witht hehelpof a special methodological approac hare analyzed. The methodical approach to the evaluation of investment efficiency of constructionis developed, which is based on the magnitude of the multiplier of capital investment in construction inthelong-termperiodandrefinedtheboundariesoftheretrospectivehorizon, which are necessary to determine such a multiplier. The rapid importance of aninvestment multiplier of construction isestablis hedand a methodological approach to qualitative interpretation of this indicator issubstantiated. The basis of a methodological approach is the results of a cluster analysis of aninvestment multiplier in the contex to fvarioustypesofconstructionandregions, the methodof K-medium, aswellaspostulatesofthetheoryoffuzzysets. Within the framework of the developed methodological approach, the "investment attractiveness of construction" characteristicsis presentedin the form of a fuzz yterm-shear, which combines three terms: "Lowefficiency", "averageefficiency", "highlevelofefficiency". Inaccordance with descriptiv estatistics of thereceived clusters, the parameters and type of functions of affiliation, the boundaries of clusters that directly affecttheuse of correctivea mendments to the value of the economic effectof capitalinvestment to the level of the contractor-executor of construction work are substantiated. The sizeofther is kfactorisestablishedtakingintoaccountthetypeofconstructionandmedium-layervalues ​​ofmultipliersofcapitalinvestmentinconstruction. Theuse of the proposed Metdic approach to the analysis of investment efficiency inconstruction makesitpossible to increase the accuracy of calculations on th epre-investmentst age of construction, aswellastoimprovemonitoring of capital investment development, carried out in the process of implementing national investment programs and international investment projects.